Pengenalan HPL Furniture Berbasis Multimedia Digital Menggunakan Teknik Motion Graphic - Ely Purnawati (Media Aplikom, 2022)
The business opportunities in the furniture sector are still promising and have a large market share. However, in recent times, the condition of the HPL Furniture business in Cilacap has seen a decline in turnover. One of the problems faced is because the majority of consumers are still limited to the surrounding villages. The number of consumers also began to decrease and most of them did not make repeated orders. They wants to expand market coverage in order to reach new potential customers. However, the lack of strategy and the lack of promotional media materials are obstacles in itself to be able to introduce their products to the public. The purpose of this research is to introduce HPL Furniture to a wider scope with digital multimedia-based technology. The method used is MDLC (Multimedia Development Life Cycle) which includes six activity cycles, namely the concept, design, material collecting, assembly, testing and distribution. The result of the research is the introduction of HPL Furniture has been successfully carried out by creating a digital multimedia-based system in the form of videos using motion graphic techniques.